Intratumoral functional heterogeneity and chemotherapy - Sipos, Ferenc (Baishideng Publishing Group Co., Limited, 2014)
Intratumoral heterogeneity including genetic and nongenetic mechanisms refers to biological differences amongst malignant cells originated within the same tumor. Both, cell differentiation hierarchy and stochasticity in gene expression and signaling pathways may result in phenotypic differences of cancer cells. Since a tumor consists of cancer cell clones that display distinct behaviours, changes in clonal proliferative behavior may also contribute to the phenotypic variability of tumor cells. There is a need to reveal molecular actions driving chemotherapeutic resistance in colon cancer cells. In general, it is widely hypothesized that therapeutic resistance in colorectal cancer is a consequence of the preferential survival of cancer stem cells. However, recent data regarding colorectal cancer suggest that resistance to anticancer therapy and post-therapeutic tumor reappearence could be related to variations of clonal dynamics. Understanding the interaction of genetic and nongenetic determinants influencing the functional diversity and therapy response of tumors should be a future direction for cancer research.